Mapping the patterns and problems in using rural library services among rural youth in Malaysia - Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva; Bolong, Jusang; Hamzah, Azimi (Sage Publications, 2015)
This study attempts to discover the pattern of rural library usage among rural youth in Malaysia and to determine the problems that are associated with such usage. The findings of this study provide an insight into youth usage of rural library services. The most obvious pattern that resulted from the findings is the connection between library usage and the availability of reading materials. Furthermore, it was found that some of the respondents raised their concern with regard to rural libraries being congested with children. A number of recommendations have been highlighted and it is expected that these can be used by concerned parties to further improve and develop rural library services.